Metabolome Comparison of Bioactive and Inactive Rhododendron Extracts and Identification of an Antibacterial Cannabinoid(s) from Rhododendron collettianum. Issue 5 (13th June 2017) - Hakeem Said, Inamullah; Rezk, Ahmed; Hussain, Ishtiaq; Grimbs, Anne; Shrestha, Abhinandan; Schepker, Hartwig; Brix, Klaudia; Ullrich, Matthias S.; Kuhnert, Nikolai
Abstract: Introduction: The science of metabolomics offers the possibility to measure full secondary plant metabolomes with limited experimental effort to allow identification of metabolome differences using principal component analysis (PCA) and partial least squares discriminant analysis (PLS‐DA) of liquid chromatography mass spectrometry (LC‐MS) data. Objective: To demonstrate a bioinformatics driven hypothesis generator for identification of biologically active compounds in plant crude extracts, which is validated by activity guided fractionation. Methodology: Crude extracts of Rhododendron leaves were tested for their antibacterial activity using agar diffusion and minimum inhibitory concentration assays. Extracts were profiled by LC‐MS. PCA and PLS‐DA were used for differentiation of bioactive and inactive extracts and their metabolites. Preparative‐high performance liquid chromatography (HPLC) and nuclear magnetic resonance (NMR) spectroscopy were used for separation and structure elucidation of pure compound(s) respectively. Results: An antibacterial Rhododendron collettianum was compared to a series of inactive extracts. Three metabolites were found to distinguish R. collettianum from other species indicating the ability of PCA and PLS‐DA to suggest potential bioactive substances. An activity‐guided fractionation of R. collettianum extracts was carried out and cannabiorcichromenic acid (CCA) was identified as antibacterial compound thereby validating the PCA and PLS‐DA generated hypothesis. Four mammalian cell lines were used to estimate possible cytotoxicity of CCA. Conclusion: It was shown that bioinformatics tools facilitate early stage identification of a biologically active compound(s) using LC‐MS data, which reduce complexity and number of separation steps in bioactive screening. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Principal component analysis (PCA) and partial least squares discriminant analysis (PLS‐DA) using liquid chromatography mass spectrometry (LC‐MS) data of 14 Rhododendron leaf extracts was carried out, in which an antibacterial extract was compared to a series of inactive extracts generating a hypothesis for potential bioactive compounds. Subsequent activity guided fractionation resulted in identification of a cannabinoid as bioactive constituent confirming the bioinformatics driven hypothesis. Cytotoxicity assays using mammalian cell lines, revealed that the antibacterial cannabiorcichromenic acid did not exhibit cytotoxicity at the concentrations exerting antibacterial activity.